Computer vision – ECCV 2016 : 14th European Conference, Amsterdam, the Netherlands, October 11-14, 2016, Proceedings /: 14th European Conference, Amsterdam, the Netherlands, October 11-14, 2016, Proceedings. Part VI : (2016) - Unknown
No abstract available